Comparison of Adrenocorticotropic Hormone Stimulation Test Results Started 2 versus 4 Hours after Trilostane Administration in Dogs with Naturally Occurring Hyperadrenocorticism. (26th May 2014) - Bonadio, C.M.; Feldman, E.C.; Cohen, T.A.; Kass, P.H.
<x xml:space="preserve">Abstract</x> Background Trilostane medical treatment of naturally occurring hyperadrenocorticism (NOH) in dogs is common, as is use of the adrenocorticotropic hormone (ACTH) stimulation test (ACTHst) in monitoring response to treatment. There is uncertainty regarding when the ACTHst should be started relative to time of trilostane administration. Objective To compare ACTHst results in dogs being treated for NOH with trilostane when the test is begun 2 versus 4 hours after trilostane administration. Animals Twenty‐one privately owned dogs with NOH, each treated with trilostane for at least 30 days. Methods Each dog had 2 ACTHst completed, 1 started 2 hours and the other 4 hours after trilostane administration. The second test was started no sooner than 46 hours and no later than 74 hours after the first. Results For all 21 dogs, the mean post‐ACTH serum cortisol concentration from tests started 2 hours after trilostane administration (5.4 ± 3.7 μg/dL) was significantly lower (P = .03) as compared with results from the tests started 4 hours after administration (6.5 ± 4.5 μg/dL). Conclusions Results of ACTHst started at different times yield significantly different results. Dogs with NOH, treated with trilostane, and monitored with ACTHst results should have all of their subsequent ACTHst tests begun at or about the same time after trilostane administration.